2001
DOI: 10.1021/bi010353q
|View full text |Cite
|
Sign up to set email alerts
|

Metal Ion-independent Association of Factor VIII Subunits and the Roles of Calcium and Copper Ions for Cofactor Activity and Inter-Subunit Affinity

Abstract: Factor VIII circulates as a divalent metal ion-dependent heterodimer comprised of a light chain (LC) and a heavy chain (HC). Reassociation of factor VIII subunits was assessed using fluorescence energy transfer where LC and HC were labeled with acrylodan (Ac; fluorescence donor) and fluorescein-5-maleimide (Fl; fluorescence acceptor), respectively. The reduction of donor fluorescence due to the acceptor was used as an indicator of binding. Subunits associated with high affinity (K(d) = 53.8 nM) in the absence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
96
1
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(111 citation statements)
references
References 33 publications
11
96
1
3
Order By: Relevance
“…Two-stage Chromogenic Factor Xa Generation Assay-The rate of conversion of factor X to factor Xa was monitored in a purified system (19) according to methods previously described (20,21). Briefly, factor VIII (1 nM) in buffer containing 20 mM HEPES, pH 7.2, 0.1 M NaCl, 0.01% Tween 20, 0.01% bovine serum albumin, 5 mM CaCl 2 , and 10 M PS/PC/PE vesicles (Buffer A) was activated with 20 nM ␣-thrombin for 1 min.…”
Section: Methodsmentioning
confidence: 99%
“…Two-stage Chromogenic Factor Xa Generation Assay-The rate of conversion of factor X to factor Xa was monitored in a purified system (19) according to methods previously described (20,21). Briefly, factor VIII (1 nM) in buffer containing 20 mM HEPES, pH 7.2, 0.1 M NaCl, 0.01% Tween 20, 0.01% bovine serum albumin, 5 mM CaCl 2 , and 10 M PS/PC/PE vesicles (Buffer A) was activated with 20 nM ␣-thrombin for 1 min.…”
Section: Methodsmentioning
confidence: 99%
“…The rate of conversion of FX to FXa was monitored in a purified system (25) according to methods previously described (26,27). FVIII (1 nM) in 20 mM HEPES, 0.1 M NaCl, 5 mM CaCl 2 , 0.01% Tween 20, 0.01% BSA, pH 7.2 (HEPES buffer), containing 20 ÎŒM PSPCPE vesicles (PS:PC:PE = 3:2:5) was activated with 30 nM α-thrombin for 1 min.…”
Section: Fxa Generation Assaymentioning
confidence: 99%
“…Experimental evidence has demonstrated that both factor V and VIII bind a single copper atom (31,32). A functional role for copper in factor V or Va has not yet been ascertained, but, in factor VIII, a type II copper leads to Ï·100-fold affinity between the factor VIII subunits (33). In our structure, ligands to the Cu 2Ï© include His-1802, His-1804 (both predicted), and Asp-1844 in a trigonal planar coordination geometry.…”
Section: Domain Interfacesmentioning
confidence: 99%